2008
DOI: 10.1186/1758-2652-10-4-78
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Treatment Access in a Population‐based Cohort of HIV‐positive Men and Women Living in Argentina

Abstract: ObjectiveTo report emerging data on the use of highly active antiretroviral therapy (HAART) in Argentina by assessing patterns of HAART access and late vs early treatment initiation in a population-based cohort of adults infected with HIV type-1.DesignThe Prospective Study on the Use and Monitoring of Antiretroviral Therapy (PUMA) is a study of 883 HIV-positive individuals enrolled in the Argentinean drug treatment program. Individuals were 16 years of age and older and were recruited from 10 clinics across Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 17 publications
(22 reference statements)
1
11
0
1
Order By: Relevance
“…Although this sampling method may present limitations regarding generalizability, online surveys via internet-based social/sexual networking may reach an often hidden population of MSM in Latin America (Curioso et al, 2007; Marcus et al, 2009; Young et al, 2015). This is important given the concentration of the HIV/AIDS epidemic among MSM in Latin America (Bastos et al, 2008) and evidence that these individuals may delay ART initiation because of high levels of HIV stigma, resulting in poorer subsequent HIV/AIDS health outcomes (Zala et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this sampling method may present limitations regarding generalizability, online surveys via internet-based social/sexual networking may reach an often hidden population of MSM in Latin America (Curioso et al, 2007; Marcus et al, 2009; Young et al, 2015). This is important given the concentration of the HIV/AIDS epidemic among MSM in Latin America (Bastos et al, 2008) and evidence that these individuals may delay ART initiation because of high levels of HIV stigma, resulting in poorer subsequent HIV/AIDS health outcomes (Zala et al, 2008). …”
Section: Discussionmentioning
confidence: 99%
“…Prior research has examined parts of the HIV treatment cascade among MSM in select countries, including Argentina (Carballo-Dieguez et al, 2014), Peru (Sanchez et al 2007), and Brazil (Kerr et al, 2013). These studies have found low HIV testing rates, with less than half of MSM participants having been tested for HIV in Argentina (Carballo-Dieguez et al, 2014) and Brazil (Kerr et al, 2013), high HIV prevalence (14–17%; Carballo-Dieguez et al, 2014; Kerr et al, 2013), and lower rates of ART initiation among MSM (i.e., compared to non-MSM counterparts in Argentina; Zala et al, 2008). …”
Section: Introductionmentioning
confidence: 99%
“…After initiating HAART, transitions will be limited to three final stages containing patients initiating a new or first HAART regimen, patients under successful therapy and patients under non-suppressive therapy. During this last phase of the simulation, rates and probabilities obtained from literature and describing toxicity of HAART regimens [21], success in achieving undetectable viral load [22], [23], [24], discordant responses to treatment [22] and viral rebound [21] are included. Also, viral load and CD4 count are modified according to the different treatment outcomes and in a magnitude that resembles that previously reported in the literature [2], [22], [25], [26].…”
Section: Methodsmentioning
confidence: 99%
“…Zala et al also reported limited use of HAART in Argentina, and in particular, noted that initiation of HAART was associated with older age, AIDS-defining illness, lower CD4 cell count and higher viral load. 24 Drug shortages and insufficient monitoring of response to HAART has also been reported. 25 In contrast, more recent data from the EuroSIDA Cohort, a prospective study of HIV-infected persons in Europe, Israel, and Argentina, reported that, in Argentina, over 95% of HIV-infected persons with a CD4 cell count <350 cells/mm 3 were receiving HAART.…”
Section: Discussionmentioning
confidence: 99%